Question Simplify the expression −6x2 Evaluate −3x2−3x2Collect like terms by calculating the sum or difference of their coefficients (−3−3)x2Solution −6x2 Show Solution Find the roots x=0 Evaluate −3x2−3x2To find the roots of the expression,set the expression equal to 0 −3x2−3x2=0Subtract the terms More Steps Simplify −3x2−3x2Collect like terms by calculating the sum or difference of their coefficients (−3−3)x2Subtract the numbers −6x2 −6x2=0Change the signs on both sides of the equation 6x2=0Rewrite the expression x2=0Solution x=0 Show Solution